Three Algorithms for Converting Control Flow Statements from Python to XD-M - Wang, Jiarui; Zhang, Nan; Duan, Zhenhua (Algorithmic Aspects in Information and Management, 2022)
This paper presents an approach to show how to implement three complex statements: continue, break, return of Python to XD-M language. To this end, three algorithms for implementing three complex statements are given in detail. Further, three complex statements are implemented in XD-M. Finally, a program example is presented to illustrate how to use the proposed approach to build an XD-M program equivalent to the original Python program.